Ilocano Irrigation The Corporate Resolution - Lewis, Henry T. (University of Hawai'i Press, 1991)
This volume examines some of the major factors-social, demographic, and environmental-that account for the success of communal irrigation in Ilocos Norte and, by implication, its absence in adjacent areas, other parts of the Philippines, and, more widely, in other parts of insular Southeast Asia. However, whether this explanation accounts for all the factors involved, or even adequately weighs those that are here discussed, is secondary to the main concern of this volume: corporate groups. What zanjeras [irrigation societies] show are repeated examples of how individual farmers, working in concert, developed and employed corporate principles to the solution of a common goal or problem. It is a kind of "solution" that has been widely and effectively employed in much of human history.